Penyuluhan Dan Pendampingan Metode Salesmanship Pada Bengkel Srijaya Mobil Surabaya - Eko Yulianto, Anton; Eko Nugroho, Novianto (COVIT (Community Service of Tambusai), 2023)
The purpose of community service carried out through the activity "Counselling and Assistance on Salesmanship Methods at Srijaya Mobil Surabaya Workshop to further improve the quality of salespeople at the workshop. The company here will be introduced to the concept of how salespeople carry out salesmanship activities based on the salesmanship implementation steps commonly carried out in the personal selling process in this case marketing services and services from the Srijaya Mobil workshop. The method of implementing activities through four stages, namely: preparation, counselling Salesmanship material, Monitoring and Evaluation. The results of this activity show that there are still many step-by-step observations that must be addressed by this workshop to further improve the quality of salespeople in finding and maintaining existing customers. Keywords: Salesmanship, Step Implementasi Salesmanship